Lipid Fractions and Contrasting Risks of Coronary Artery Disease and Diabetes - White, Jon (JAMA Cardiol, 2016)
IMPORTANCE: Low-density lipoprotein cholesterol (LDL-C) is causally related to coronary artery disease (CAD), but the relevance of HDL-C and triglycerides is uncertain. LDL-C lowering by statins modestly increases diabetes risk, but it is unknown if this effect is specific to statins. OBJECTIVE: To investigate the relationships of three routinely measured lipid fractions with CAD and diabetes through Mendelian randomization (MR), using conventional MR and making use of newer approaches such as multivariate MR and MR-Egger that addresses pleiotropy of genetic instruments. DESIGN: We used published data from genome wide association studies to construct genetic instruments and applied them to investigate associations between lipid fractions and risk of CAD and diabetes using MR approaches that took into account pleiotropy of genetic instruments. MAIN OUTCOMES AND MEASURES: coronary artery disease and diabetes RESULTS: We constructed genetic instruments composed of 130 SNPs for LDL-C (explaining 7.9% of its variance), 140 SNPs for HDL-C (6.6% of variance) and 140 SNPs for triglycerides (5.9% of variance). A 1-SD (genetically instrumented) elevation in LDL-C (equivalent to 38 mg/dL) and triglycerides (equivalent to 89 mg/dL) were associated with higher CAD risk: odds ratios (OR) and 95% confidence intervals (CI) were 1.68 (1.51-1.87) for LDL-C and 1.28 (1.13-1.45) for triglycerides. The corresponding OR for HDL-C (equivalent to a 16mg/dL increase) was 0.95 (0.85-1.06). All three lipid traits were associated with a lower risk of diabetes. The OR and 95% CI limits were 0.79 (0.71-0.88) for LDL-C and 0.83 (0.76-0.90) for HDL-C. CONCLUSIONS AND RELEVANCE: Routinely measured lipid fractions exhibit contrasting relationships with risk of CAD and diabetes. Increased LDL-C, HDL-C and TG are associated with reduced risk of diabetes. This information will be relevant to design of clinical trials of lipid modifying agents, which should carefully monitor for dysglycemia and incidence of diabetes.